Environmental taxation and revenue for development - Agnar Sandmo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
This paper considers the role of global environmental taxes both as instruments for improving the global environment and as a source of revenue for funding economic development. It reviews the general case for environmental taxes and the particular issues that arise for the adoption of such taxes in an international setting without a single jurisdiction. It also discusses the possibilities for political acceptance of such taxes when tax revenue is linked to the goal of economic development. The revenue potential of global environmental taxes is evaluated with special reference to a global carbon tax. It is found that this tax alone has the potential to raise sufficient revenue to finance the United Nations' Millennium Development Goals.
Keywords: H23; H87; O13; 330; environment; taxation; carbon tax; consumption; Ökosteuer; Entwicklung